(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper aims at proposing a critical framework addressed at the environmental justice movement: a deanthropocentrization of the subject – through the recognition of the intrinsic worth of nature, and its procedural shades – may lead to the decolonization of the environment itself. Through examples such as the Ecuadorian recognition of Pachamama, and the acknowledgement of Maori lands as right-bearing entities in New Zealand, the framework builds on the adaptation of collective memories theories, intended as environmental collective memories, to operationalize Eric Yamamoto’s “4Rs” approach, based on Recognition, Responsibility, Reconstruction, and Reparation, in a nature-related context.